The genus Sisyphus Latr. (coleoptera : scarabaeidae) in Southern Africa - Paschalidis, Karen Margaret (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1975)
1. Twenty four species of the genus Sisyphus known in southern Africa are listed with their synonyms and their taxonomy is discussed. 2. A key to the adults of 23 of these species is given. 3. The known distribution of 23 species and seasonal occurrence of 19 species are illustrated and briefly discussed. 4. The general biology of the genus Sisyphus is discussed and the major behavioural and biological differences between the two subgenera Sisyphus and Neosisyphus are given. 5. The laboratory and field investigation into variations in behaviour and biology in eight species occurring in the Mkuzi Game Reserve, with regards to interspecific competition, is presented. 6. The known possible natural enemies of Sisyphus are mentioned and the extent of competition from other genera, based on field and laboratory observations, is outlined. 7. Summary tables of all data with a final tabulated evaluation of the suitability of species for introduction into Australia is given. 8. Nine species have been highly recommended for Australia. Six more species could be considered but most of these still need further investigation. The remaining nine species were found to be unsuitable for transfer to Australia.
Keywords: Beetles -- Africa, Southern; Scarabaeidae -- Africa, Southern